THE INFLUENCE OF HUMAN RESOURCE COMPETENCE, APPLICATION OF GOVERNMENTAL ACCOUNTING STANDARDS AND REGIONAL FINANCIAL ACCOUNTING SYSTEMS ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORTS (EMPIRICAL STUDIES ON THE GOVERNMENT OF LAMONGAN AND TUBAN) - Dientri, Abdul Manaf; Darmayanti, Novi; Rama, Radian Sri; Sa’diyah, Salimatus (LPPM UNISDA, 2024)
ABSTRACT Study aims to examine the effect of human resource competence, application of governmental accounting standards and regional financial accounting systems on the quality of local government financial reports (Empirical studies on the government of Lamongan and Tuban). This research was conducted in Lamongan and Tuban involving 40 employees of the Lamongan BPPKAD and Tuban BPPKAD as respondents. This quantitative study uses multiple linear regression. The technique is processed with SPSS 25 to analyze several hypotheses. The intercorrelation model between the three variables in this study reveals that the competence of human resources, the application of government accounting standards and the application of regional financial accounting systems have a significant correlation with the quality of local government financial reports. Keyword: Human Resources, Government Accounting Standards, Financial Accounting Systems